An Electrochemical and Photoelectron Spectroscopy Study of a Low Temperature Liquid Metal Battery Based on an Ionic Liquid Electrolyte. Issue 10 (1st January 2016) - Lalau, Cornel-Constantin; Dimitrova, Anna; Himmerlich, Marcel; Ispas, Adriana; Weier, Tom; Krischok, Stefan; Bund, Andreas
Abstract : We report the design of a low-temperature liquid metal battery (LMB). Li and Ga as the negative and positive electrode, respectively, are used in combination with a room temperature ionic liquid as an electrolyte. 1 mol/L lithium bis(trifluoromethylsulfonyl)imide (Li[TFSI]) in 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide is chosen as electrolyte. The battery operates at 220°C which is a relatively low temperature for a LMB and shows good electrochemical performance at low current density. The cells were cycled for more than 600 h and achieved a round-trip Coulombic efficiency close to 100% and an average voltage efficiency of 66% resulting in an overall energy efficiency of 65%. At higher current densities, however, the system showed up to 75% irreversible capacity loss after three cycles. To understand the origin of this strong deterioration, we characterized the surface and the bulk properties of the Ga cathode using X-ray Photoelectron Spectroscopy. Especially at higher current densities a decomposition of the electrolyte was found. The chemical changes that occurred and the elemental distribution at the Ga cathode are analyzed based on XPS measurements at different stages of the battery charge/discharge cycling.